2005
DOI: 10.1002/aoc.938
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic bioaccumulation and species in marine polychaeta

Abstract: Published whole tissue arsenic concentrations in polychaete species tissues range from 1.5-2739 µg arsenic/g dry mass. Higher mean total arsenic concentrations are found in deposit-feeding polychaetes relative to non-deposit-feeding polychaete species collected from the same locations. However, mean arsenic concentrations at some of the locations are skewed by the high arsenic concentrations of Tharyx marioni. There appears to be no direct correlation between sediment arsenic concentrations and polychaete arse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…There is evidence that high concentrations of As can accumulate in microbes and plants [11][12][13]65,66]. It has been reported that the marine polychaeta accumulated As concentrations up to 2739 mg/kg (dry mass) [66].…”
Section: As Hyperaccumulation In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that high concentrations of As can accumulate in microbes and plants [11][12][13]65,66]. It has been reported that the marine polychaeta accumulated As concentrations up to 2739 mg/kg (dry mass) [66].…”
Section: As Hyperaccumulation In Plantsmentioning
confidence: 99%
“…It has been reported that the marine polychaeta accumulated As concentrations up to 2739 mg/kg (dry mass) [66]. However, As accumulation in Table 3 Reported As-hyperaccumulating plants and their performance…”
Section: As Hyperaccumulation In Plantsmentioning
confidence: 99%
“…High arsenic concentrations can be accumulated in microbes (e.g., bacteria, fungi, and algae) and plants even from substrates containing low concentrations (Kaise et al, 1997;Waring and Maher, 2005). It has been reported that marine Polychaete species could accumulate arsenic concentrations up to 2739 mg/kg (dry weight, Waring and Maher, 2005).…”
Section: Bioaccumulationmentioning
confidence: 99%
“…It has been reported that marine Polychaete species could accumulate arsenic concentrations up to 2739 mg/kg (dry weight, Waring and Maher, 2005). Takeuchi et al (2007) reported that arsenic accumulation in Marinomonas communis cells amounted to 2290 mg arsenic/kg (dry weight) when incubated on a medium containing 5 mg As(V)/L.…”
Section: Bioaccumulationmentioning
confidence: 99%
“…The situation is similarly serious for Hg contamination (McCormack, 2014). As is chemical species that may be bioaccumulated throughout the aquatic food chain, which is of concern from the perspective of human exposure (Bryan and Langston, 1992;Waring and Maher, 2005;Casado-Martinez et al, 2010). Previous work has indicated that Hg had an irreversible influence on organisms of the trophic food chains due to biomagnification (Fisher et al, 1984;Mathews and Fisher, 2008).…”
Section: Introductionmentioning
confidence: 99%